S-Rater: data mining application in Islamic financial sector - Kartiwi, Mira; Arundina, Tika; Omar, Mohd Azmi; Gunawan, Teddy Surya (IEEE, 2014)
Islamic finance and capital market is one of the fastest growing segments of international financial markets. Recent innovations in Islamic finance and capital market have changed the terrain of the landscape of the financial industry. One of them is Islamic securities which are known as Sukuk. The use of Sukuk as the alternative to the existing conventional bond, has become increasingly popular in the last few years. They are used as a means of raising government finance through sovereign Sukuk issues, and means through which companies raise funds by issuing corporate Sukuk. In addition, theoretically there should be some differences in rating methodologies for bond and Sukuk because these two instruments are different in nature. Thus, it is the aim of this study to identify the important determinants in Sukuk Rating using data mining approach. The final model is then implemented into web application, called S-Rater.